L’usage du jeu sérieux comme outil de prospective des usages du véhicule autonome : méthodologie et enjeux à partir de l’expérience du jeu de plateau RoboSpectif - Olivier Klein (Netcom Association, 2020)
In a context of expanding the field of thought on autonomous vehicles, the LAET have produced the desk game "RoboSpectif", This paper deals firstly with the theoretical framework which is the base of this game. It presents the reasons why we choose a gaming method to produce prospective data. It addresses the methodological issues of RoboSpectif’s conception and its main principles and rules. It looks back on the first experiences of diffusion of this game, in order to access which public it applies. At last, it deals with limits of this game device to produce data.